(untitled) (American Journal of Business Management, Economics and Banking, 2026)
The article examines the root causes of international migration from Uzbekistan through the lens of demographic and socio-economic development. It focuses on the challenges of employing a growing population, infrastructure deficits in regions, and low-income levels in rural areas. The study concludes with recommendations aimed at creating conditions for legal and protected migration.